The Dynamics of Social Capital in Croatia, 1995-2003 - Štulhofer, Aleksandar (Array, 2004)
The concept of social capital has gained wide acceptance and use in social sciences, particularly in sociology, political science and institutional economics. Its popularity should be primarily attributed to various societal benefits, theoretically and empirically well explored, linked to the production and persistence of social capital. This paper reconsiders the dynamics of social capital in Croatia presented in a previous article (Štulhofer, 2003a). Using data from two cross-sectional nationally representative social surveys (World Values Survey – Croatia 1995, and South East European Social Survey, 2003), the authors focus on the dynamics of social capital during the 1995–2003 period. In spite of economic growth, increasing political stability and advancing democratization in the observed period, the findings point to the erosion of social capital. The main factors behind the negative dynamics of social capital in Croatia seem to be growing perception of corruption and declining religiousness.